Earth Scientists and Sustainable Development: Geocomputing, New Technologies, and the Humanities - Sebastiano Trevisani; Pietro Daniel Omodeo (Land, 2021)
This opinion paper discusses some of the challenges and opportunities that earth scientists face today in connection with environmental problems. It focuses on aspects that are related to the role of geocomputational approaches and new technologies for geoenvironmental analysis in the context of sustainable development. The paper also points out a “data imbalance” effect, a key issue in the analysis of environmental evolution and of geosphere-anthroposphere interactions in the long-term. In connection with this, it stresses the importance of geoenvironmental information which can be derived from environmental humanities and related disciplines, such as history and archeology. In this context, the complexities and potentialities of a dialogue between earth sciences and the humanities are outlined.